2020
DOI: 10.1212/wnl.0000000000009370
|View full text |Cite
|
Sign up to set email alerts
|

Scrambler therapy improves pain in neuromyelitis optica

Abstract: ObjectiveTo determine whether Scrambler therapy is an effective, acceptable, and feasible treatment of persistent central neuropathic pain in patients with neuromyelitis optica spectrum disorder (NMOSD) and to explore the effect of Scrambler therapy on co-occurring symptoms.MethodsWe conducted a randomized single-blind, sham-controlled trial in patients with NMOSD who have central neuropathic pain using Scrambler therapy for 10 consecutive weekdays. Pain severity, pain interference, anxiety, depression, and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…While the e cacy of scrambler therapy in central neuropathic pain has rarely been investigated, we observed a favorable treatment outcome in the patients with spinal cord lesions of various etiologies including myelitis, ischemia, vascular malformation and subacute combined degeneration. In keeping with our results, a recent sham-controlled study involving 22 patients with neuromyelitis optica spectrum disorder showed that scrambler therapy can improve pain, depression, and anxiety 38 . The bene ts of scrambler therapy for central neuropathic pain deserve further investigations.…”
Section: Discussionsupporting
confidence: 91%
“…While the e cacy of scrambler therapy in central neuropathic pain has rarely been investigated, we observed a favorable treatment outcome in the patients with spinal cord lesions of various etiologies including myelitis, ischemia, vascular malformation and subacute combined degeneration. In keeping with our results, a recent sham-controlled study involving 22 patients with neuromyelitis optica spectrum disorder showed that scrambler therapy can improve pain, depression, and anxiety 38 . The bene ts of scrambler therapy for central neuropathic pain deserve further investigations.…”
Section: Discussionsupporting
confidence: 91%
“…The studies focused on pain without diagnostic specification ( 18 , 25 , 51 ), neuropathic pain ( 26 , 28 , 49 , 50 , 53 , 55 , 56 ), one study on neuropathic pruritus ( 52 ), painful tonic spasms ( 29 32 ), ON-related headache ( 54 ), and a description of diverse pain types ( 2 , 27 ). One randomized single blind sham-controlled trial studied the effect of Scrambler therapy in NMOSD patients with central neuropathic pain ( 55 ). All other studies ( n = 17) were descriptive and non-interventional.…”
Section: Resultsmentioning
confidence: 99%
“…The trial showed pain reduction from a median baseline numeric rating scale (NRS) pain score of 5.0-1.5 after 10 days of treatment. The median NRS score did not significantly decrease in the sham arm (55). Currently, the lack of clear guidelines regarding the frequency and stimulation amplitude necessary to achieve sufficient pain reduction currently limits the use of TENS (57,198,199).…”
Section: Fourth-line Therapymentioning
confidence: 88%
See 2 more Smart Citations